Science, commerce, and control : patronage and the development of antropological archaeology in the americas. - Snead, James E. (American Antropological Association, 1999)
At the end of the nineteenth century, the drive to "professionalize" anthropology in the United States promoted the development of particular patterns of interaction between archaeologists and their patrons, which had a significant impact on the conduct of research. The expansion of fieldwork and the acquisition of collections required the financial backing of sponsors, whose own ambitions often diverged from those of the scholars whom they supported. This essay explores shifts in patron-professional relationships in southwestern archaeology at the turn of the century, using the case of the Hyde Expedition to Chaco Canyon (1896-1909).